First report of myroides phaeus bacteraemia identified by polymerase chain reaction and genetic sequencing - Silva Caso, Wilmer Gianfranco (2019)
We report the first case of Myroides phaeus isolated from blood, causing bacteremia in an immunocompromised patient using the automated MicroScan Walk Away 96 system, followed by bacterial identification by amplication-sequencing of the 16S rDNA. The sequences obtained were compared with the reference sequence of the BLAST platform - National Library of Medicine, USA, and the isolation was identified as Myroides phaeus strain with 99.67% identity in Blast report. In the literature we did not find previous reported cases of infections by this bacterium, however its pathogenic role is still controversial; therefore, this isolation alerts us to carry out an exhaustive surveillance of other possible acquisition routes.